Genetic parameters and environmental effects on temperament score and reproductive traits of Nellore cattle - Barrozo, D. [UNESP]; Buzanskas, M. E. [UNESP]; Oliveira, J. A. [UNESP]; Munari, D. P. [UNESP]; Neves, H. H. R. [UNESP]; Queiroz, S. A. [UNESP] (Cambridge University Press, 2012)
Animal temperament is a trait of economic relevance and its use as a selection criterion requires the identification of environmental factors that influence this trait, as well as the estimation of its genetic variability and interrelationship with other traits. The objectives of this study were to evaluate the effect of the covariates dam age at calving (ADC), long yearling age (YA) and long yearling weight (YW) on temperament score (T) and to estimate genetic parameters for T, scrotal circumference (SC) at long YA and age at first calving (AFC) in Nellore cattle participating in a selection program. The traits were analyzed by the restricted maximum likelihood method under a multiple-trait animal model. For all traits, contemporary group was included as a fixed effect and additive genetic and residual as random effects. In addition to these effects, YA, YW and ADC were considered for analyzing T. In the case of SC and AFC, the effect of long YW was included as a covariate. Genetic parameters were estimated for and between traits. The three covariates significantly influenced T. The heritability estimates for T, SC and AFC were 0.18 +/- 0.02, 0.53 +/- 0.04 and 0.23 +/- 0.08, respectively. The genetic correlations between T and SC, and T and AFC were -0.07 +/- 0.17 and -0.06 +/- 0.19, respectively. The genetic correlation estimated between SC and AFC was -0.57 +/- 0.16. In conclusion, a response to selection for T, SC and AFC is expected and selection for T does not imply correlated responses with the other traits.
Keywords: age at first calving; scrotal circumference; long yearling age; long yearling weight